Cost-Effectiveness of Treatment Wetlands for Nitrogen Removal in Tropical and Subtropical Australia - Emad Kavehei (MDPI AG, 2021)
Treatment wetlands can reduce nitrogen (N) pollution in waterways. However, the shortage of information on their cost-effectiveness has resulted in their relatively slow uptake in tropical and subtropical Australia, including the catchments of the Great Barrier Reef and Moreton Bay. We assessed the performance of constructed treatment wetlands (CW) and vegetated drains (VD) that treat agricultural runoff, and of sewage treatment plant wetlands (STPW), which polish treated effluent. Treatment performance was estimated as changes in concentration (dissolved inorganic nitrogen, DIN, and total nitrogen, TN; mg L−1) and annual load reductions (kg N ha−1 yr−1). We calculated their cost-effectiveness by comparing their N removal against the costs incurred in their design, construction, and maintenance. Overall, CWs and VDs reduced DIN concentrations by 44% (0.52 to 0.29 mg L−1), and STPW reduced them by 91% (2.3 to 0.2 mg L−1); STPWs also reduced TN concentrations by 72%. The efficiency varied among sites, with the best performing CWs and VDs being those with relatively high inflow concentrations (>0.2 mg L−1 of DIN, >0.7 mg L−1 of TN), low suspended solids, high vegetation cover and high length: width ratio. These high performing CWs and VDs removed N for less than USD 37 kg−1 DIN (AUD 50 kg−1 DIN), less than the end-of-catchment benchmark for the Great Barrier Reef of USD 110 kg−1 DIN (AUD 150 kg−1 DIN). When adequately located, designed, and managed, treatment wetlands can be cost-effective and should be adopted for reducing N in tropical and subtropical Australia.